The protective effects of caffeic acid phenethyl ester (CAPE) against liver damage induced by cigarette smoke inhalation in rats - Pekmez, Hidir; Kus, Ilter; Colakoglu, Neriman; Ogeturk, Murat; Ozyurt, Huseyin; Turkoglu, Asli Ozdem; Sarsilmaz, Mustafa (Wiley, 2007)
The aim of this study was to investigate the histological and biochemical changes in liver of rats exposed to cigarette smoke and effects of caffeic acid phenetyl ester (CAPE) on these changes. For this purpose, 21 male Wistar rats were divided into three groups. Animals in Group I were used as control. Rats in Group II were exposed to cigarette smoke and rats in Group III were exposed to cigarette smoke and injected daily with CAPE. At the end of the 60-days experimental period, all rats were killed by decapitation and blood samples were obtained. Serum alanine aminotransferase (ALT), aspartate aminotransferase (AST), total bilirubin levels and hepatic superoxide dismutase (SOD) and glutathione peroxidase (GSH-Px), malondialdehyde (MDA) contents were determined. Following routine histological procedures, liver tissue specimens were examined under a light microscope. The levels of ALT, AST, total bilirubin, SOD, GSH-Px and MDA were significantly increased in rats exposed to cigarette smoke compared with those of the controls. Light microscopic examination of liver specimens from rats exposed to cigarette smoke revealed mononuclear cell infiltration and that some of the hepatocytes had a hyperchromatic nucleus and enlarged sinusoids. The rats which were treated with CAPE along with cigarettes had partially attenuated histological changes associated with cigarette exposure. In conclusion, the damage inflicted by cigarette in the rat liver can be partially prevented by CAPE administration. Copyright (C) 2005 John Wiley & Sons, Ltd.
Keywords: caffeic acid phenetyl ester; oxidative damage; liver; cigarette smoke